The Relationship between Learning Motivation and Learning Outcomes of Students Chemistry of Grade XI-MNS in 4 State SHS Pematangsiantar - Hisar Marulitua Manurung; Suprapto Manurung (PendIPA Journal of Science Education, 2021)
This study aimed to determine the relationship between learning motivation and learning outcomes of students chemistry of grade XI-MNS (mathematics and natural science). The research design used was quantitative with a correlation approach. The population of this study was all students of class XI-MNS at state senior high school (SHS) 4 Pematangsiantar as many as 205 students for the 2019/2020 Academic Year. The sampling technique for this research was random sampling, which is a random sampling technique with a total sample of 40 students. The instrument used in the study was a non-test (questionnaire) of 20 questions to measure student learning motivation, but measuring chemistry learning outcomes was taken from the odd semester exam scores. The results showed that the percentage of high motivation was 20%, sufficient motivation was 50%, and low motivation was 30%. Student chemistry learning outcomes with a minimum score with a score of 41 and a maximum value with a score of 63 derived from the semester test scores that have been assessed by the field teacher. The correlation coefficient (r) in this study is 0.80 and the value of the coefficient of determination (r²) amounting to 0.63 which indicates that students' chemistry learning outcomes affect 63% changes in chemistry learning motivation. This results show that the relationship between learning motivation and learning outcomes of students chemistry of grade XI-MNS is very strong.